2002
DOI: 10.1042/bj20020256
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency increases the expression of inducible nitric oxide synthase in RAW 264.7 macrophages: role of nuclear factor-κB in up-regulation

Abstract: The inducible isoform of nitric oxide synthase (iNOS) is implicated in atherosclerosis, malignancy, rheumatoid arthritis, tissue and reperfusion injuries. A key determinant of the pro-oxidant versus protective effects of NO is the underlying redox status of the tissue. Selenoproteins, such as glutathione peroxidases (GPxs) and thioredoxin reductases, are key components of cellular defence and promote optimal antioxidant/oxidant balance. In this study, we have investigated the relationship between Se status, iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 34 publications
3
97
0
3
Order By: Relevance
“…Se supplementation increased 15d-PGJ 2 in a Cox-1-dependent manner, which can form a 15d-PGJ 2 -IKKb adduct that inhibits IjB kinase b (IKKb) activity. This mechanism may explain earlier data showing that Se-deficient macrophages exhibit increased LPS-induced NFjB activation and subsequent Cox-2 expression, iNos expresson, and NO production compared with Se-supplemented macrophages (199,279). As expected, lower Se status in these macrophages increased intracellular ROS, consistent with other data showing increased ROS with decreased selenoprotein expression in macrophages (35).…”
Section: Se and Eicosinoid Synthesis In Macrophagessupporting
confidence: 90%
“…Se supplementation increased 15d-PGJ 2 in a Cox-1-dependent manner, which can form a 15d-PGJ 2 -IKKb adduct that inhibits IjB kinase b (IKKb) activity. This mechanism may explain earlier data showing that Se-deficient macrophages exhibit increased LPS-induced NFjB activation and subsequent Cox-2 expression, iNos expresson, and NO production compared with Se-supplemented macrophages (199,279). As expected, lower Se status in these macrophages increased intracellular ROS, consistent with other data showing increased ROS with decreased selenoprotein expression in macrophages (35).…”
Section: Se and Eicosinoid Synthesis In Macrophagessupporting
confidence: 90%
“…LPS treatment to cells signiˆcantly elevated NO generation by 36 times more than the LPS-untreated negative control, which has been well-documented by several researchers. [7][8][9][10]31) Genistein was found to suppress NO production in a concentration-dependent manner with an IC50 of 69.4 mM (Fig. 1).…”
Section: Resultsmentioning
confidence: 93%
“…[1][2][3][4] It has been reported that NFkB is sensitive to oxidative modiˆcation of a particular cysteine at position 62 in p50, which is essential for DNA binding. 6) Furthermore, antioxidants such as carnosol, 7) anthocyanins, 8) selenium, 9) and organosulfur compounds 10) have been reported to suppress NO production in macrophages and their inhibition mechanisms are based on their abilities to inhibit the activation of NFkB. Numerous animal studies have been supported the idea that intraperitoneal injection of LPS to animals elevated oxidative stress and treatment with antioxidants before LPS challenge ameliorated oxidative damages, specially in decreasing the production of ROS.…”
mentioning
confidence: 99%
“…In fact, selenium deficiency in human Jurkat and lung carcinoma cells increased the nuclear binding and transcriptional activation of oxidative-stress responsive genes by nuclear factor-B (NF-B) (16). Along the same lines, studies in our laboratory have shown that selenium supplementation of macrophages decreased the expression of two pro-inflammatory genes, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase, via the inactivation of NF-B, whereas the expression of COX-1 was unaffected (17,18). It is well known that signaling pathways activated by ligation of cell surface pattern recognition receptors converge at the IB kinase (IKK) complex that phosphorylates the inhibitory subunit and cytoplasmic retention protein of the NF-B complex, IB␣ (19).…”
mentioning
confidence: 95%